Can PROMIS domains of pain and physical functioning detect changes in health over time for children with sickle cell disease?. Issue 5 (6th February 2020) - Singh, Ashima; Dasgupta, Mahua; Simpson, Pippa M.; Brousseau, David C.; Panepinto, Julie A.
Abstract: Background: The Patient‐Reported Outcomes Measurement Information System (PROMIS) includes multiple domains that measure pain and physical functioning which are valid and reliable for use in children with sickle cell disease. The responsiveness of these measures to detect changes in health status over time among children with sickle cell disease is unknown. Procedure: We conducted a prospective cohort study of children presenting to emergency department (ED) with vaso‐occlusive crises. Children completed PROMIS surveys in the ED and at two follow‐up time points (7‐10 days and 1‐3 months) after their acute care visit. Linear mixed models were used to determine if there were significant changes in PROMIS T scores over time. We used a patient's global assessment of change in pain question to anchor the changes in PROMIS scores (mean and 95% confidence interval). A change was considered statistically significant if the 95% CI did not include 0. Results: We found that patients improved significantly in all domains 1 to 3 months after discharge from an acute care visit for pain. In addition, the pain and physical stress experience domains were responsive to change 7 to 10 days after discharge. Using the anchor of change in pain, for children who had considerable improvement in pain, there were significant changes in PROMIS T scores ranging from 6 to 15. Conclusions: Relevant PROMIS domains detect changes in children experiencing acute vaso‐occlusive crises. These domains can be used in research and clinic settings to measure clinically relevant change in children with sickle cell disease.